35.1k views
4 votes
Which is the simplified form of the expression?

12n-1/2(6n-4)

Answers
9n-2
9n+2
15n-2
15n-8

2 Answers

3 votes

Let's simplify step-by-step.

12n−1/2(6n−4)

Distribute:

=12n+−3n+2

Combine Like Terms:

=12n+−3n+2

=(12n+−3n)+(2)

=9n+2

Answer:

=9n+2

User Parmanand
by
5.7k points
3 votes

Answer:

9n+2

Explanation:

first distribute the -1/2 to 6n-4 from there you will get -3n+2.

second add like terms (12n-3n+2) you will add 12n and -3, this will give you 9n.

after that since you don't have any other like term your answer stays as 9n+2

User Jon Colverson
by
6.1k points